ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG KONSUMEN SMARTPHONE SAMSUNG PADA TOKO PONSEL CEMPAKA CELL DI KABUPATEN SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Pratiwi, Dwi; Soeliha, Siti; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The aim of the study was to determine the Analysis of the Effect of Price and Product Quality on Consumer Repurchase Interests of Samsung Smartphones at Cempaka Cell Cell Phone Shops in Situbondo Regency with Consumer Satisfaction as an Intervening Variable. The sampling technique used in this study was simple random sampling of 97 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that price has a positive and significant effect on consumer satisfaction, product quality has a positive and significant effect on consumer satisfaction, price has a positive and significant effect on repurchase intention, product quality has a negative and significant effect on interest repurchase, consumer satisfaction has a positive and significant effect on repurchase intention, price has a positive and significant effect on repurchase intention through consumer satisfaction, product quality has a positive and significant effect on repurchase intention through consumer satisfaction